Sistem Pendukung Keputusan Pemberian Kredit pada Koperasi Karyawan Aneka Pangan Nusantara Menggunakan Metode SAW - Lusa Indah Prahartiwi; Nurul Fatimah (Universitas Bina Sarana Informatika, 2023)
Giving credit is an effort made by cooperatives to provide loans to members by utilizing the funds they have. In granting credit, cooperatives need to study and calculate appropriately so that there are no mistakes in decision making. The Aneka Pangan Nusantara Purwakarta Employee Cooperative is a cooperative engaged in various business fields, such as shops, savings and loans, and various businesses. Based on the results of interviews that have been conducted with Mr. Tendi Rismawan as Administrator, it is known that in making credit decisions at the Aneka Pangan Nusantara Purwakarta Employee Cooperative, it is still carried out directly by the Chairman, Treasurer, and Sie. Savings and Loans cooperative. As a result, if many members apply for loans, the decision-making process becomes ineffective and efficient and can create opportunities for errors to occur, therefore a system is needed that can assist in making decisions. Decision Support System (DSS) is a computer-based information system that helps decision makers to make quick and accurate decisions on a semi-structured problem. DSS in this study used the Simple Additive Weighting (SAW) method. The SAW method was chosen because it can give the highest priority to members who apply for loans. The dataset in this study consisted of 3 criteria and 16 alternatives. The results showed that those who were entitled to a credit loan were Suprianto and Jimmi Oktavianus. The application of a decision support system using the SAW method can provide solutions based on predetermined criteria to determine the priorities and priorities of members who apply for loans in providing credit